2020
DOI: 10.1016/j.bmcl.2019.126876
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the incorporation of lysine derivatives into proteins with methylester forms of unnatural amino acids

Abstract: We have improved the incorporation of L-and D-forms of unnatural amino acid (UAA) N εthiaprolyl-L-lysine (ThzK) into ubiquitin (UB) and green fluorescent protein (GFP) by 2-6 folds with the use of the methylester forms of the UAAs in E coli cell culture. We also improved the yields of UAA-incorporated UB and GFP with the methylester forms of N ε -Boc-L-Lysine (BocK) and N ε -propargyl-L-Lysine (PrK) by 2-5 folds compared to their free acid forms. Our work demonstrated that using methylester-capped UAAs for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…We cultured the cells in media supplemented with 1 mM L-ThzK-OMe 1. As previously reported, [11] we could express the UB K48ThzK mutant with a yield of more than 20 mg per liter of cell culture, determined as the amount of protein eluted from the Ni-NTA column (Figure 1A). UB K48ThzK 2 was then treated with O-methylhydroxyamine to generate the UB K48CysK mutant 3, and the conversion of the thiazolidine ring to the 1,2-aminothiol functionality was confirmed by the decrease of the MW of UB as measured by MALDI-MS (Figure S1A-B).…”
supporting
confidence: 59%
See 3 more Smart Citations
“…We cultured the cells in media supplemented with 1 mM L-ThzK-OMe 1. As previously reported, [11] we could express the UB K48ThzK mutant with a yield of more than 20 mg per liter of cell culture, determined as the amount of protein eluted from the Ni-NTA column (Figure 1A). UB K48ThzK 2 was then treated with O-methylhydroxyamine to generate the UB K48CysK mutant 3, and the conversion of the thiazolidine ring to the 1,2-aminothiol functionality was confirmed by the decrease of the MW of UB as measured by MALDI-MS (Figure S1A-B).…”
supporting
confidence: 59%
“…We cultured the cells in media supplemented with 1 mM L‐ThzK‐OMe 1 . As previously reported, [11] we could express the UB K48ThzK mutant with a yield of more than 20 mg per liter of cell culture, determined as the amount of protein eluted from the Ni‐NTA column (Figure 1A).…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations
“…It has been demonstrated that methyl ester form of UAAs against free acid form showed much better yield; the improved yield is possibly due to the improved membrane permeability of the methyl ester forms of the UAAs to E. coli cells as compared to the free acid forms, even though the same tRNA synthetases and E. coli strains were used for incorporation. 129 A study in 2020 optimized the direct incorporation of a uorescent UAA (7-hydroxy-4-coumarin-yl)ethyl glycine, where MS methods conrm that the UAA is introduced at only one site and that there is limited precedent. 116 The biochemical implications of altering the cellular translation machinery, as employed in GCE-based tagging, have yet to be extensively explored.…”
Section: Conclusion Limitations and Future Perspectivesmentioning
confidence: 99%